Cluster illumination differentially affects growth of fruits along their ontogeny in highbush blueberry (Vaccinium corymbosum L.). - Godoy, Carlos A. (2018)
Shading highbush blueberry plants generally leads to a delayed fruit development. Experiments have been performed to study the effects of light on fruit growth independently from the rest of the canopy. Clusters were shaded during different fruit growth periods. The equatorial diameter of the fruits as a function of days after full bloom followed a double-sigmoidal growth pattern, being fitted using a Gompertz II nonlinear mixed model, and absolute growth rates were obtained from each fitted model. Both whole-cycle shaded and second-stage shaded fruits showed a delayed peak in absolute growth curves with respect to both first-stage shaded and whole-cycle unshaded controls. Our results suggest that deficiency of light during the last stage of highbush blueberry fruits may lead to a substantial delay (of about 10–16 days) in harvest as compared with well-illuminated fruits. In order to estimate the contribution of intrinsic fruit photosynthesis to its own growth at different stages, clusters were subjected to girdling on their peduncles at different times. Girdling just before the second-stage resulted in fruits gaining between 35 and 40% of dry weight in comparison with the controls. This suggests that fruit photosynthesis may play a relevant role in fruit growth during the second sigmoidal stage, which in turn may contribute to explain the delayed growth observed in shaded fruits.